Genetic Determinism: A Modern Challenge to Islamic Belief in Human Freedom of Choice - Abdullah, Fatimah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Genetic Determinism: A Modern Challenge to Islamic Belief in Human Freedom of Choice